Progressive sudomotor dysfunction in amyotrophic lateral sclerosis. Issue 1 (1st July 2002) - Beck, M; Giess, R; Magnus, T; Puls, I; Reiners, K; Toyka, K V; Naumann, M
Abstract : Autonomic dysregulation is part of the complex degenerative process in amyotrophic lateral sclerosis (ALS). To investigate this, sweating was examined at rest in 39 patients with ALS in comparison with a control group. Sweat was collected over a 30 second period over the thenar and hypothenar eminences and on the sole of the foot, using a commercial device based on vapour pressure gradient. The measurements were repeated after three and six months in 10 patients for longitudinal analysis. In early ALS, patients had significantly higher skin water loss than control subjects over the thenar and the hypothenar eminences. In advanced disease stages, sweating was decreased at all sites compared with controls. A significant decline in sweat secretion of about 40% was found over a six month period. The findings suggest an abnormal sympathetic activity with hyperhidrosis in early ALS and a reduction in sweat production as the disease progresses.